2011
DOI: 10.4049/jimmunol.1100885
|View full text |Cite
|
Sign up to set email alerts
|

B Cell-Derived IL-15 Enhances CD8 T Cell Cytotoxicity and Is Increased in Multiple Sclerosis Patients

Abstract: Multiple lines of evidence suggest that CD8 T cells contribute to the pathogenesis of multiple sclerosis (MS). However, the sources and involvement of cytokines such as IL-15 in activating these cells is still unresolved. To investigate the role of IL-15 in enhancing the activation of CD8 T cells in the context of MS, we determined cell types expressing the bioactive surface IL-15 in the peripheral blood of patients and evaluated the impact of this cytokine on CD8 T cell cytotoxicity and migration. Flow cytome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
66
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 61 publications
(70 reference statements)
2
66
0
Order By: Relevance
“…This effect was previously described for CD8 + T cells and NK cells (24,52). In our study, expression of NKG2D, perforin, granzyme B, and IFN-g were increased, as well as the frequency of degranulating cells.…”
Section: T Cellssupporting
confidence: 58%
See 2 more Smart Citations
“…This effect was previously described for CD8 + T cells and NK cells (24,52). In our study, expression of NKG2D, perforin, granzyme B, and IFN-g were increased, as well as the frequency of degranulating cells.…”
Section: T Cellssupporting
confidence: 58%
“…In MS patients, both soluble and membrane-bound IL-15 levels are increased in the serum and cerebrospinal fluid (29)(30)(31). Recently, increased IL-15 expression was found on peripheral B cells and on astrocytes within brain lesions of MS patients, compared with control subjects (24,32). The cytotoxicity-enhancing effect of IL-15 has already been described for NK cells and CD8 + T cells (24,(32)(33)(34).…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Two recent studies have shown that B cell-derived IL-15 (Schneider et al, 2011) and astrocyte-derived IL-15 enhance CD8 + T cell cytotoxicity in MS patients (Saikali et al, 2010). Except for ␥␦T1 and ␥␦T17 cells, it is unclear whether ␥␦T cells secrete …”
Section: Introductionmentioning
confidence: 97%
“…P40 is a subunit of IL-12 and IL-23 and although less well studied, the p40 monomer as well as the p40 2 homodimer have been identified. 3 Importantly, IL-12 and IL-23 are thought to play central roles in CD4 T cell polarization and phenotypic plasticity favoring either a Th1 or a Th17 response. 10 Despite 10-fold concentration of CSF, measurements of most soluble mediators (13/16 tested) including IL-12 and IL-23 were below the detection limit of the assays used, suggesting that such CSF monitoring is not helpful as a measure of treatment efficacy.…”
Section: Study Of a Subgroup Of Patients With Msmentioning
confidence: 99%